The lipidome and proteome of oil bodies from Helianthus annuus (common sunflower) - Furse, S.; Liddell, S.; Ortori, C.; Williams, H.; Neylon, Cameron; Scott, D.; Barrett, D.; Gray, D. (2013)
In this paper we report the molecular profiling, lipidome and proteome, of the plant organelle known as an oil body (OB). The OB is remarkable in that it is able to perform its biological role (storage of triglycerides) whilst resisting the physical stresses caused by changes during desiccation (dehydration) and germination (rehydration). The molecular profile that confers such extraordinary physical stability on OBs was determined using a combination of 31P/1H nuclear magnetic resonance (NMR), high-resolution mass spectrometry and nominal mass-tandem mass spectrometry for the lipidome, and gel-electrophoresis-chromatography-tandem mass spectrometry for the proteome. The integrity of the procedure for isolating OBs was supported by physical evidence from small-angle neutron-scattering experiments. Suppression of lipase activity was crucial in determining the lipidome. There is conclusive evidence that the latter is dominated by phosphatidylcholine (~60 %) and phosphatidylinositol (~20 %), with a variety of other head groups (~20 %). The fatty acid profile of the surface monolayer comprised palmitic, linoleic and oleic acids (2:1:0.25, 1H NMR) with only traces of other fatty acids (C24:0, C22:0, C18:0, C18:3, C16:2; by MS). The proteome is rich in oleosins (78 %) with the remainder being made up of caleosins and steroleosins. These data are sufficiently detailed to inform an update of the understood model of this organelle and can be used to inform the use of such components in a range of molecular biological, biotechnological and food industry applications. The techniques used in this study for profiling the lipidome throw a new light on the lipid profile of plant cellular compartments.